2016
DOI: 10.1016/j.phrs.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Structure, mechanism and therapeutic utility of immunosuppressive oligonucleotides

Abstract: Synthetic oligodeoxynucleotides that can down-regulate cellular elements of the immune system have been developed and are being widely studied in preclinical models. These agents vary in sequence, mechanism of action, and cellular target(s) but share the ability to suppress a plethora of inflammatory responses. This work reviews the types of immunosuppressive oligodeoxynucleotide (Sup ODN) and compares their therapeutic activity against diseases characterized by pathologic levels of immune stimulation ranging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 104 publications
(173 reference statements)
4
36
0
Order By: Relevance
“…Our findings show that Sup ODN treatment significantly reduced the influx of inflammatory cells into the lungs and their production of pro-inflammatory cytokines, effects expected to reduce VILI (34). No clinically detectable adverse events (e.g., labored breathing, hemorrhage, infection, death) were observed in follow up periods ranging from 6-48 h, consistent with reports that Sup ODN are safe in rodents and non-human primates (18,22). Findings in this murine model support the further assessment of Sup ODN for the prevention/treatment of VILI.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings show that Sup ODN treatment significantly reduced the influx of inflammatory cells into the lungs and their production of pro-inflammatory cytokines, effects expected to reduce VILI (34). No clinically detectable adverse events (e.g., labored breathing, hemorrhage, infection, death) were observed in follow up periods ranging from 6-48 h, consistent with reports that Sup ODN are safe in rodents and non-human primates (18,22). Findings in this murine model support the further assessment of Sup ODN for the prevention/treatment of VILI.…”
Section: Discussionsupporting
confidence: 88%
“…Our group and others have studied a class of suppressive oligodeoxynucleotide (Sup ODN) that specifically inhibits inflammatory reactions (18,19). Sup ODN block macrophage activation and down-regulate the production of proinflammatory and Th1 cytokines (20,21) by inhibiting activation cascades utilizing STAT1, STAT3, STAT4 and the interferon-inducible protein AIM2 (19,(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…The immune regulation using G-rich sequences is known to require relatively high ODN concentrations [65,66]. Usually, cellular uptake of ODNs is a crucial step for their interaction with a wide range of molecular targets because nucleic acids being polyanions cannot passively diffuse across cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The LNs enrichment was consistent with our previous observations, where lipid-modified ODNs bound endogenous albumin and transported to the LNs (19). In contrast, unmodified ODN quickly diffused into blood circulation due to its small molecular size and exhibited minimal LNs accumulation (19,27). Flow cytometry analysis of the cells in the LNs revealed that CD11c+ dendritic cells and F4/80+ macrophages were the major cells responsible for the uptake of lipo-A151.…”
Section: Discussionmentioning
confidence: 99%